Enhancing mechanical response of a 96.5Sn-3.0Ag-0.5Cu solder using energy efficient microwave assisted sintering route - Nai, S.M.L. (2014)
The Minerals, Metals and Materials Society - 3rd International Conference on Processing Materials for Properties 2008, PMP III